2018
DOI: 10.1016/s0140-6736(17)32714-9
|View full text |Cite|
|
Sign up to set email alerts
|

Percutaneous coronary intervention in stable angina (ORBITA): a double-blind, randomised controlled trial

Abstract: SummaryBackground Symptomatic relief is the primary goal of percutaneous coronary intervention (PCI) in stable angina and is commonly observed clinically. However, there is no evidence from blinded, placebocontrolled randomised trials to show its efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
471
0
30

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 805 publications
(540 citation statements)
references
References 35 publications
(19 reference statements)
12
471
0
30
Order By: Relevance
“…There is no evidence from the papers included in this review that PCI is cost-effective when compared with other competing treatment options. Therefore the current cost-effectiveness evidence does not support the increased use of PCI that has been seen in Australia and internationally, and there is increasingly reduced evidence of clinical effectiveness 32 .…”
Section: Confidence In Changing Services Based On Current Evidencementioning
confidence: 99%
“…There is no evidence from the papers included in this review that PCI is cost-effective when compared with other competing treatment options. Therefore the current cost-effectiveness evidence does not support the increased use of PCI that has been seen in Australia and internationally, and there is increasingly reduced evidence of clinical effectiveness 32 .…”
Section: Confidence In Changing Services Based On Current Evidencementioning
confidence: 99%
“…Use of placebo control in PCI is achievable, as demonstrated in ORBITA. 5 Importantly, ethical concerns, which limited follow-up to 6 weeks in this trial, are less and less pressing with the accumulating evidence of prognostic neutrality of PCI. With longer follow-up, a broader range of end points could be assessed and the uncertain role of PCI in stable coronary disease may finally be defined.…”
Section: A Definitive Trial With Definitive Design: Ischemiamentioning
confidence: 99%
“…For instance, 1 grant body reviewer rejected funding for ORBITA (Objective Randomized Blinded Investigaton with optimal medical Therapy or Angioplasty in stable angina), 5 the first truly blinded randomized controlled trial of PCI, because another trial had used an impartial end point committee: …”
Section: The Meaning Of Blindingmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The recently presented Objective Randomised Blinded Investigation with optimal medical Therapy of Angioplasty in stable angina (ORBITA) trial cast some doubt on the effectiveness of PCI on symptom burden in stable CAD when assessed in a blinded, randomized placebo-controlled fashion. 10 There is abundance of literature on the prognostic value of MPI in patients with stable CAD which allows for its use in risk stratification. [11][12][13] While the COURAGE trial did not demonstrate a benefit of coronary revascularization on hard cardiovascular events in patients with stable CAD, 5 a seminal retrospective study suggested that MPI may be useful to guide coronary revascularization.…”
mentioning
confidence: 99%